Does serum butyrylcholinesterase level determine the severity and mortality of COVID-19 pneumonia?: Prospective study - Sipahioglu, Hilal; Esmaoglu, Aliye; Kiris, Ayse; Dursun, Zehra Bestepe; Kuzuguden, Sibel; Cavus, Mine Altinkaya; Artan, Cem (Frontiers in Medicine, 2022)
Background: The WHO emphasized the importance of knowing the risk factors for the severity of the disease in the COVID-19 pandemic. Our aim in this study was to determine the relationship between serum Butyrylcholinesterase (BChE) level, which is rapidly affected by inflammation, and the severity of COVID1-9 pneumonia and mortality. Methods: Patients diagnosed with COVID-19 pneumonia between March and May 2021 were included in the study. The patients were divided into two groups as severe and mild to moderate pneumonia according to the WHO's guidelines. Serum BChE levels were studied by ELISA method from the blood samples taken from the patients on the day of hospitalization. The severity of the disease and other factors affecting hospital mortality were also evaluated. Results: 147 patients with COVID-19 pneumonia were included in this study. Of these patients, 58% had severe pneumonia and 42% had mild to moderate pneumonia. The BChE level was median 13 (IQR: 11.2-21.5)ng/ml in patients with severe COVID-19 pneumonia and median 20(IQR: 10-35.7)ng/ml in patients with mild to moderate pneumonia. Hospital with mortality rate was higher in patients with low BChE levels. However, statistically, BChE hasn’t associated mortality in COVID-19 pneumonia (OR 1.002(0.957-1.049) p:0.490). CRP, procalcitonin, lactate, and D-dimer levels were associated mortality in COVID-19 pneumonia. Conclusion: Being not statistically significant, the mortality rate was higher in patients with low BChE levels. BChE level is an important marker in determining the severity of COVID-19 pneumonia. Early prediction of the severity of COVID-19 pneumonia will enable early planning of the treatment process.